Design and validation of an observational instrument to basketball referee evaluation (IOVAB) - García-Santos, D.; Ibáñez, S. J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
The aim of this research was to design and validation of an observation instrument for assessing the behavior of a basketball referee (IOVAB). In the process of validation and reliability of the instrument are involved fourteen experts judges. The subjects selected to be part of experts judges had to meet four to six of the established selection criteria. The construct validity was calculated through Aiken´s V and confidence intervals. To check the reliability of the instrument was used Cronbach´s α. The observation instrument is divided in six contents blocks: uniformity, presence and physical condition, sign and general mechanics refereeing, violations rules, fouls, cooperation with partner and match control. Only six of the fifty items of instrument obtained Aiken´s V low values enough to be removed. The reliability of the instrument was acceptable with a value of .712. The IOVAB design final was prepared attend the qualitative and quantitative assessments by experts.